Confinement of Ultrasmall Bimetallic Nanoparticles in Conductive Metal–Organic Frameworks via Site‐Specific Nucleation. Issue 38 (2nd August 2021) - Park, Chungseong; Koo, Won‐Tae; Chong, Sanggyu; Shin, Hamin; Kim, Yoon Hwa; Cho, Hee‐Jin; Jang, Ji‐Soo; Kim, Dong‐Ha; Lee, Jiyoung; Park, Seyeon; Ko, Jaehyun; Kim, Jihan; et al.
Abstract: Conductive metal–organic frameworks (cMOFs) are emerging materials for various applications due to their high surface area, high porosity, and electrical conductivity. However, it is still challenging to develop cMOFs having high surface reactivity and durability. Here, highly active and stable cMOF are presented via the confinement of bimetallic nanoparticles (BNPs) in the pores of a 2D cMOF, where the confinement is guided by dipolar‐interaction‐induced site‐specific nucleation. Heterogeneous metal precursors are bound to the pores of 2D cMOFs by dipolar interactions, and the subsequent reduction produces ultrasmall (≈1.54 nm) and well‐dispersed PtRu NPs confined in the pores of the cMOF. PtRu‐NP‐decorated cMOFs exhibit significantly enhanced chemiresistive NO2 sensing performances, owing to the bimetallic synergies of PtRu NPs and the high surface area and porosity of cMOF. The approach paves the way for the synthesis of highly active and conductive porous materials via bimetallic and/or multimetallic NP loading. Abstract : Ultrasmall bimetallic nanoparticles (BNPs) are confined in pores of 2D conductive metal–organic frameworks (cMOFs). BNPs in cMOFs significantly improve the NO2 ‐sensing performance, owing to the bimetallic synergies of PtRu NPs and the high surface area and porosity of the cMOF.